2021
DOI: 10.1002/bit.27785
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor production of rVSV‐based vectors in Vero cell suspension cultures

Abstract: The Vero cell line is the most used continuous cell line in viral vaccine manufacturing. This adherent cell culture platform requires the use of surfaces to support cell growth, typically roller bottles, or microcarriers. We have recently compared the production of rVSV-ZEBOV on Vero cells between microcarrier and fixed-bed bioreactors. However, suspension cultures are considered superior with regard to process scalability. Therefore, we further explore the Vero suspension system for recombinant vesicular stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Our results are in agreement with previous studies conducted by Elahi et al ( 2019 ) and Gélinas et al ( 2019 ) showing that shifting to 34°C (from 37°C) led to a threefold or sixfold increase in virus titer. In addition, the production of a VSV‐based Ebola vaccine showed a preference for production at 34°C (Gélinas et al, 2019 , 2020 ; Kiesslich et al, 2021 ). These results led us to test an additional lower temperature value of 31°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with previous studies conducted by Elahi et al ( 2019 ) and Gélinas et al ( 2019 ) showing that shifting to 34°C (from 37°C) led to a threefold or sixfold increase in virus titer. In addition, the production of a VSV‐based Ebola vaccine showed a preference for production at 34°C (Gélinas et al, 2019 , 2020 ; Kiesslich et al, 2021 ). These results led us to test an additional lower temperature value of 31°C.…”
Section: Resultsmentioning
confidence: 99%
“…Production of various VSV‐based vaccines in Vero cells has been reported. However, all reported processes were either in microcarriers (Kiesslich et al, 2020; Mangion et al, 2020) or in cell suspension (Kiesslich et al, 2021) and none were reported in a Fibra‐Cel based production process. Before optimizing the process parameters in the Ambr15 system, a preliminary study was conducted (Jayson et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Sousa et al [ 14 ] developed a scalable bioprocess for Peste des Petites Ruminants virus (PPRV) vaccine production in Vero cells using SFM, microcarrier technology in STB, in-situ cell detachment from microcarriers and perfusion. Recently, Vero cells have been successfully adapted to grow in suspension in serum-free media [ 15 , 16 ]. Fujii et al [ 17 ] fabricated an ultrasonic irradiation system and used CHO cells as a model example, and they found the culture time was reduced by 14% when the cell number increased 1000-fold.…”
Section: Introductionmentioning
confidence: 99%
“…VERO cells are derived from African green monkey kidney and act as hosts for ERV and SARS-CoV-2, which is a good model for this study. VERO cells are also widely used in the study of the molecular mechanism of virus infection, as well as the production of vaccines and recombinant proteins, and are regarded as an ideal cell model for cultivating influenza vaccines and studying the molecular mechanism of virus infection [ 60 , 61 , 62 ]. VERO cells could not secrete interferon α/β when infected with a virus because of their inherent genetic defects.…”
Section: Discussionmentioning
confidence: 99%